(untitled) (Ameghiniana, 2016)
Over the last decades, Paleogene outcrops in northwestern Argentina have been yielding abundant information about the evolution of South American mammals during the early Cenozoic. This region was an important area of early diversification for several groups of native ungulates, particularly notoungulates, during the Eocene. Although many specimens were found in association with postcranial elements, most reports describe cranial material. It is well known that these postcranial elements can provide characters for phylogenetic analyses and important clues for paleobiological inferences. This study presents a series of postcranial remains (proximal tarsals) from the Geste Formation exposed in Antofagasta de la Sierra, Catamarca Province, Argentina. Three calcanei and two astragali are herein described, compared to those of extinct ungulates and taxonomically identified. A functional analysis allows inferring the association of these bones to different types of stances. One calcaneus is assigned to Toxodontidae (Notoungulata) and exhibits some plantigrade features. Presenting digitigrade-like morphology, the other two calcanei and an incomplete astragalus are assigned to Interatheriidae (Notoungulata). Another astragalus, characterized by a configuration suggesting a digitigrade posture, is assigned to Didolontidae Ernestokokenia cf. E. yirunhor. The study of the tarsal provides a more integrative view of the Paleogene forms of the region as well. Resumen. ESTUDIO ANATÓMICO Y SISTEMÁTICO DE TARSALES PROXIMALES DE UNGULADOS DE LA FORMACION GESTE (NOROESTE DE ARGENTINA). Los afloramientos paleógenos del noroeste de Argentina han brindado en los últimos años una abundante cantidad de información acerca de la evolución de los mamíferos de América del Sur durante la primera parte del Cenozoico. Esta región constituyó durante el Eoceno una importante zona de radiación y diversificación temprana para varios grupos de mamíferos. Hasta el momento, la mayoría de los reportes describen material craneal, si bien en muchos casos dichos materiales se encuentran en asociación con elementos postcraneales. Estos últimos pueden brindar caracteres para análisis filogenéticos e importantes indicios acerca de la paleobiología de los taxones. En el presente trabajo se estudia una muestra de restos postcraneanos provenientes de la Formación Geste aflorante en Antofagasta de la Sierra, provincia de Catamarca, Argentina. Se describen tres calcáneos y dos astrágalos que fueron comparados con ungulados extintos y determinados sistemáticamente. Un análisis funcional permite inferir la asociación de estos huesos con los diferentes tipos de posturas. Un calcáneo es asignado a un Toxodontia (Notoungulata) y presenta algunas características de plantígrados. Los otros dos calcáneos, junto a un astrágalo incompleto, son referidos a Interatheriidae (Notoungulata), exhibiendo morfologías propias de digitígrados. Otro astrágalo es referido al Didolontidae Ernestokokenia cf. E. yirunhor; su configuración sugiere una postura digitígrada. El estudio de los tarsales brinda, además, una visión más integradora de las formas paleógenas de la región.